Alcohol Use Disorder Among Textile Workers: Evidence from Ethiopia - Belete, Habte (Journal of drug issues, 2024)
Little is known about its prevalence of Alcohol Use Disorder (AUD) and its work-based etiology among employed adults in developing countries. To address this knowledge gap, we surveyed a total of 423 Ethiopian textile workers (of whom 313 were non-abstaining) assessing AUD. Using the Alcohol Use Disorders Identification Test or “AUDIT” and categorizing an AUD as any AUDIT score of 16 or greater, the prevalence of AUD was estimated at 4.3% among overall participants and 5.8% among non-abstainers. Logistic regression analysis identified younger age, work-related disability, and stress as significantly associated with AUD. Given the link between these potential work-related risk factors and AUD, the findings suggest that alcohol use prevention programs such as peer-led counseling and/or Employment Assistance Programs, along with brief interventions, may be useful in addressing potential AUD risk factors, reducing AUD prevalence and associated sequaelae, and treating workers with AUD in developing countries.